Force-touch measurement methodology based on user experience - Choonsung Nam; DongRyeol Shin (International Journal of Distributed Sensor Networks)
The touch interface is an input method widely used in smart devices. Recently, new touch interface which supports force value has been introduced. The force-touch interface adds a factor called depth to the plane coordinates as compared to the existing touch interface. Despite the advantages of force-touch, which can provide touch position and force intensity information with one input, there are still many devices that cannot support force values. To provide them with a force-touch interface, we developed a force-touch cover for existing smart devices that do not support the existing force value. It is a way to provide the force value to the smart device by recognizing the force value through the sensor installed in smartphone case. However, it is difficult to apply the force value obtained through such a device directly to the force-touch interface, because it is necessary to distinguish between force touch and general touch. Therefore, in order to use the force-touch interface using the force-touch cover proposed in this article, the force value measured at the time of general touch is analyzed by user experiment to set the general touch area. Also, an area outside the general touch area is set as the force-touch area. In the force-touch and general touch area, the area is applied considering the error of the force value actually measured in the developed force-touch cover. Therefore, in this article, we analyze the force value input through the proposed force-touch cover and find a reference value that can distinguish force touch from general touch by user experiment and propose a method to apply it.